Human Factors in Aviation - Salas, Eduardo; Salas, Eduardo; Maurino, Dan (Elsevier Science, 2010)
This edited textbook will be a fully updated and expanded version of the highly successful first edition of Human Factors in Aviation. Written for the widespread aviation community - students, engineers, scientists, pilots, managers, government personnel, etc. ? HFA offers a comprehensive overview of the topic, taking readers from the general to the specific, first covering broad issues, then the more specific topics of pilot performance, human factors in aircraft design, and vehicles and systems.The new editors offer essential breath of experience on aviation human factors from multiple perspectives (i.e. scientific research, regulation, funding agencies, technology, and implementation) as well as knowledge about the science. The proposed contributors have all been chosen as experts in their fields.Topics carried over from the first edition will be fully updated, often by new authors who are now at the fore of the field. New material ? which will represent 50% of the volume ? will focus on the challenges facing aviation specialists today. One of the most significant developments in this decade has been NextGen, the Federal Aviation Administration's plan to modernize national airspace and to address the impact of air traffic growth by increasing airspace capacity and efficiency while simultaneously improving safety, environmental impacts and user access. NextGen issues will be covered in full. Other new topics include: High Reliability Organizational Perspective, Situation Awareness & Workload in Aviation, Human Error Analysis, Human-System Risk Management, LOSA, NOSS and Unmanned Aircraft System, (miliary aviation?).*Comprehensive textbook offering an up-to-date synthesis of primary source material which does not need to be supplemented*New edition thoroughly updated with 50% new material, offering full coverage of NexGen and other modern issues *Instructor web site with testbank and image collection makes this the only text offering ancillary support*Liberal use of case examples exposes students to real-world examples of dangers and solutions*More affordable than the less comprehensive competing volumes on market